Kerajinan Caping Desa Langko sebagai Sumber Belajar Ekonomi Berbasis Budaya Lokal Pada Mata Pelajaran Ekonomi - Sa'adati, Nurul; Muzakir, Muzakir; Adipta, Marazaenal (Tirai Edukasi : Jurnal Pendidikan, 2024)
This study aims to examine the potential of caping (bamboo hat) handicraft from Langko Village as a local culture-based learning resource in Economics subjects at SMA Islam Bina Insani Langko. A descriptive qualitative method was employed through observation, in-depth interviews, and documentation. The results reveal that caping handicraft is not only economically valuable as a source of community income but also embodies cultural, social, and entrepreneurial values that can be integrated into learning. Field findings indicate teachers’ and students’ enthusiasm in connecting the caping production process with economic concepts, such as supply-demand, production costs, and marketing. Integrating local culture into learning enhances relevance and meaningfulness while simultaneously fostering cultural preservation among younger generations.